Pola Hubungan Antara Buruh Tenun (Tembe Nggoli) Dengan Pemilik Modal Di Kelurahan Rabadompu Barat Kecamatan Raba Kota Bima - Nurnazmi Nurnazmi; Syaifullah Syaifullah; Ida Waluyati (IAI Darussalam, 2019)
The purpose of this research is to describe the pattern of relationships between Weaving Workers and capital owners. The research approach uses a qualitative approach, a phenomenological method. The main informants were 13 people and 3 supporting informants, the sampling technique used was purposive sampling. Data collection techniques using interview, observation and documentation. Data analysis techniques using data reduction, data display, and data verification. The results showed (1) the pattern of the weaver's relationship with the weaving capital, (2) the pattern of the relationship of the weaving laborer with their own capital and educational institutions, (3) the pattern of the relationship of the weaving laborer with the company / individual capital owner, (4) the pattern of the weaver's relationship with small family (nuclear family), (5) pattern of weaver relationship with extended family, (6) pattern of labor relations between weaving with KUBE, company and own capital, (7) pattern of relationship between weaving labor and small family (nuclear family) and extended family, (8) the pattern of relations between weaving workers and individual owners of capital, (9) the pattern of relations between laborers weaving with banks, and (10) the pattern of relations between workers weaving with savings and loan cooperatives, analyzed using the theory of alienation.